2021
DOI: 10.3934/mbe.2021345
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of BIRC5 plays essential role in esophageal squamous cell carcinoma

Abstract: <abstract> <sec><title>Background</title><p>Esophageal squamous cell carcinoma (ESCC) is one of the most common cancers in the world, the detection and prognosis of which are still unsatisfactory. Thus, it is essential to explore the factors that may identify ESCC and evaluate the prognosis of ESCC patients.</p> </sec> <sec><title>Results</title><p>Both protein and mRNA expression levels of BIRC5 are upregulated in ESCC group rather than no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The experiment was performed following the manufacturer's instructions. The immunohistochemical experimental methods and protein level scoring criteria were consistent with our previous study [ 19 ].…”
Section: Methodssupporting
confidence: 67%
“…The experiment was performed following the manufacturer's instructions. The immunohistochemical experimental methods and protein level scoring criteria were consistent with our previous study [ 19 ].…”
Section: Methodssupporting
confidence: 67%
“…Cytokines in lymphocytes have been shown to control the expression of BIRC5, which is essential for the growth and survival of hematopoietic cells. In the context of human cancers, BIRC5 has been reported to inhibit cell apoptosis while stimulating cell proliferation (26,27). Previous studies have revealed that BIRC5 exerts its anti-apoptotic effects through the suppression of both caspase-dependent and caspase-independent apoptotic pathways, in addition to promoting cell growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical experiments were carried out according to the instructions of the manufacturer. Experimental methods and protein level scoring criteria can be found in our previous study [12].…”
Section: Collection Of Samples and Performance Of Immunohistochemistrymentioning
confidence: 99%
“…All mRNA expression-associated data were transformed by log 2 (x + 1). Datasets with the same platform (e.g., GSE32036 and GSE4127 from GPL6884) were merged for a combined dataset after eliminating batch effects [13][14][15][16], which was similar to the published study [12].…”
Section: Data Standardization and Elimination Of Batch Effects Betwee...mentioning
confidence: 99%